2003
DOI: 10.1103/physreve.68.016407
|View full text |Cite
|
Sign up to set email alerts
|

Chaos-induced resistivity in the magnetic null region: A nonlinear mechanism of collisionless dissipation

Abstract: Magnetic null points act as scattering centers where particles describe chaotic orbits, and the mixing effect brings about increase of the kinetic entropy. The resultant "chaos-induced resistivity" may explain anomalous diffusion of current in magnetic null regions [Phys. Rev. Lett. 88, 045003 (2002)], which can be much larger than the conventional collisionless resistivity in a high temperature plasma. To study the statistical properties of the system (such as Lyapunov exponents and distribution functions), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 13 publications
3
37
0
Order By: Relevance
“…However, the roles of spatial anomalous diffusion arising from waveparticle interactions versus the role of ions nongyrotropy in generating resistivity in RCS of having widths of ion and MHD scales need further studies. We point out that Singh and Subramanian 24 compared the chaos-induced resistivity 22,23 with the resistivity given by the KAW-induced anomalous diffusion for solar flare reconnections and find comparable resistivities; these resistivities are much lower than that needed for reconnection in the magnetosphere and can be attributed to D $ 10 5 -10 6 m 2 /s for the solar coronal plasma with T e $ 100 eV and B $ 10-50 nT.…”
Section: Conclusion and Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, the roles of spatial anomalous diffusion arising from waveparticle interactions versus the role of ions nongyrotropy in generating resistivity in RCS of having widths of ion and MHD scales need further studies. We point out that Singh and Subramanian 24 compared the chaos-induced resistivity 22,23 with the resistivity given by the KAW-induced anomalous diffusion for solar flare reconnections and find comparable resistivities; these resistivities are much lower than that needed for reconnection in the magnetosphere and can be attributed to D $ 10 5 -10 6 m 2 /s for the solar coronal plasma with T e $ 100 eV and B $ 10-50 nT.…”
Section: Conclusion and Discussionmentioning
confidence: 78%
“…A novel study by Numata and Yoshida 22,23 found that the motion of charged particles in a confined region near the reconnection X-line is highly chaotic and their exit from this region gives collisionless resistivity. They used test-particle simulations to study the dynamics of electrons and ions, showing that the chaotic motion in conjunction with the exit of some of the particles energized by the reconnection electric field from the core of the diffusion region contributes to an anomalous resistivity.…”
mentioning
confidence: 99%
“…In the absence of strong particle collisions, this effective conductivity can support the reconnection process (Horton, 1997;Numata and Yoshida, 2002) and results in the formation of magnetic islands in the outflow regions. The amplitude of the corresponding effective collision frequency ν eff is proportional to the decay rate β of the number of particles in the current sheet (Numata and Yoshida, 2003). The estimate for the β parameter can be obtained from simple approximations of the time evolution of the number of particles initially injected to the current sheet.…”
Section: Discussionmentioning
confidence: 99%
“…In collisionless plasmas, where the collision mean free path can approach the system scales, anomalous sources of resistivity have been proposed [ Dupree , ; Horton and Tajima , ; Yoshida et al , ; Numata and Yoshida , ]. Resistivity can be enhanced by wave‐particle interactions [ Ji et al , ; Drake and Lee , ], stochasticity/turbulence in the magnetic fields [ Kulpa‐Dybel et al , ], and single particle motion in spatially varying magnetic fields [ Speiser , ; Lyons and Speiser , ; Horton and Tajima , ; Numata and Yoshida , []]. Lower hybrid waves have often been observed during reconnection process [ Bale et al , ].…”
Section: Introductionmentioning
confidence: 99%